On the Cost-vs-Quality Tradeoff in Make-or-Buy Decisions - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2010)
The make-or-buy decision is analyzed in a simple two-task principal-agent model. There is a cost-saving/quality tradeoff in effort provision. The principal faces a dichotomous choice between weak ("make") and strong ("buy") cost-saving incentives for the agent; the dichotomy is due to an incomplete-contracting limitation necessitating that one party be residual claimant. Choosing "buy" rather than "make" leads to higher cost-saving effort and – in a plausible "main case" – to lower quality effort; this in spite of stronger direct quality-provision incentives in the former case.
Keywords: D23; L24; L25; 330; make-or-buy decision; manipulation; outsourcing